Zad:1 Oblicz:
a) 1,25×(-3⅓)×(-8)=
b) -3×(4,2-6,3)=
c) (3⅔-4)×(6-⅗)=
d) (-3⅘-⅕)×(-3,7+1,4)=
e) (0,92-5)÷(3×0,4)=
f) (-5 1/7 - 9/14)=
g) (1⅙-5¾)×(-12)÷1,1=
h) (-⅔)²×(-12,3+3,3)=
i) (-0,3)³÷(-1+⅖)²=
j) (2,5-2⅓)²-(-⅓)³÷⅔=

P.S Proszę o całe działania :)
Z góry dziękuję ;*

1

Odpowiedzi

2009-10-19T21:40:21+02:00
A) 1,25×(-3⅓)×(-8)=(-10)*(-3⅓)=(-10)*(-10/3)=100/3=33⅓
b) -3×(4,2-6,3)=-3*(-2,1)=6,3
c) (3⅔-4)×(6-⅗)=(-⅓)*5⅖=(-⅓)*27/5=-9/5=-1,8
d) (-3⅘-⅕)×(-3,7+1,4)=(-4)*(-2,3)=9,2
e) (0,92-5)÷(3×0,4)=(-4,08):1,2=-3,4
f) (-5 1/7 - 9/14)=(-36/7-9/14)=(-72/14-9/14)=-81/14=-5 11/14
g) (1⅙-5¾)×(-12)÷1,1=(7/6-23/4)*(-12):1,1=(14/12-69/12)*(-12):1,1 = (-55/12)*(-12):1,1=55:1,1=50
h) (-⅔)²×(-12,3+3,3)=4/9*(-9)=-4
i) (-0,3)³÷(-1+⅖)² = -0,027:(1-6/5+4/25) = 0,027:(-5/25+4/25) = 0,027:(-0,04) = -0,675
j) (2,5-2⅓)²-(-⅓)³÷⅔=(6,25-1/3+49/9)-(-1/27)*3/2=(6,25+46/9)-(-1/18) = (25/4+46/9)+1/18 = (225/36+184/36)+1/18 = 409/36+2/36 = 411/36 = 11 15/36 = 11 5/12
1 5 1